Levels and Sources of Trace Metals and TPH in Aerosol Particles in Some Cities of the Niger Delta Region of Nigeria: Statistical Approach - B. O. Ekpo (Challenging Issues on Environment and Earth Science Vol. 1, 2021)
This study measured and compared seasonal levels of trace elements (Pb, Hg, Cr, Ni, V, Cu, Cd, Mn, Fe, Zn, Co, and As), total Petroleum Hydrocarbon (TPH) and Suspended Particulate Matter (PM10) in aerosols particles collected between July–September, 2005 and January–March, 2006 at four major cities (Calabar, Eket, Aba and Port Harcourt) in the Niger delta region of Nigeria. The PM10 concentrations varied between the lowest, 27.72 ± 11.33 ?g/m3 in Calabar and the highest, 75.50±25.60 ?g/m3 in Aba, while TPH ranged from 6.56 ± 3.36 µg/m3 in Calabar to the highest level of 35.95 ±16.30 µg/m3 in Eket. The results of trace metal analysis showed that the aerosols in the air basin at all sites in the Niger delta region of Nigeria contain concentrations of elements (Pb, Hg, Cr, Ni, V, Cu, Cd, Mn, Co and As) < 15 ?g/m3. Higher mean concentrations of Fe (41.26 ± 9.84 µg/m3) recorded at Calabar and Zn (39.76 ± 6.15 µg/m3) and (22.91±6.26 µg/m3) were recorded at Aba and Port Harcourt respectively. In the dry season (January – March, 2005), the mean highest TPH concentrations (35.95 ± 16.30) and (33.05 ± 16.21 µg/m3) were obtained at Aba and Eket respectively, while the lowest mean concentration (6.56 ± 3.36 µg/m3) was obtained at Calabar. Paired independent t-test at p ? 0.05 (df = 34, n = 36) confirmed significant seasonal variations in the concentrations of the metals with higher concentrations during the dry season. Enrichment factor (EF) analysis was adopted to identify the sources and their contributions to the aerosol particles. Our results revealed that the atmosphere in the studied cities was highly enriched by Pb, Hg, Cr, Ni, V, Cu, Cd, Mn, Zn, Co, and As of anthropogenic origin, in the order Port Harcourt > Aba > Eket > Calabar. Multivariate statistical (Principal Component and Cluster) analyses validated the sources of the trace metals, as well as their controls by local meteorological elements. This study provides baseline information about the region and is useful for effective environmental pollution monitoring in the Niger delta region of Nigeria.